Whose education for all? : the recolonization of the African mind - Brock-Utne, Birgit, 1938- (Garland reference library of social science, 2000)
Since 1990, when the phrase ""education for all"" was first coined at the World Bank conference in Jomtien, Thailand, a battle has raged over its meaning and its impact on education in Africa. In this thought-provoking new volume, Dr. Brock-Utne argues that ""education for all"" really means ""Western primary schooling for some, and none for others."" Her incisive analysis demonstrates how this construct robs Africans of their indigenous knowledge and language, starves higher education in Africa, and thereby perpetuates Western dominion. In Dr. Brock-Utne's words, ""A quadrangle building has